Transient flow of the oil-refrigerant mixture through the radial clearance in rolling piston compressors - Gasche, José L. [UNESP]; Ferreira, Rogério T. S.; Prata, Álvaro T. (My University, 1999)
Unsteady flow of oil and refrigerant gas through radial clearance in rolling piston compressors has been modeled as a heterogeneous mixture, where the properties are determined from the species conservation transport equation coupled with momentum and energy equations. Time variations of pressure, tangential velocity of the rolling piston and radial clearance due to pump setting have been included in the mixture flow model. Those variables have been obtained by modeling the compression process, rolling piston dynamics and by using geometric characteristics of the pump, respectively. An important conclusion concerning this work is the large variation of refrigerant concentration in the oil-filled radial clearance during the compression cycle. That is particularly true for large values of mass flow rates, and for those cases the flow mixture cannot be considered as having uniform concentration. In presence of low mass flow rates homogeneous flow prevail and the mixture tend to have a uniform concentration. In general, it was observed that for calculating the refrigerant mass flow rate using the difference in refrigerant concentration between compression and suction chambers, a time average value for the gas concentration should be used at the clearance inlet.
Keywords: Lubricating oils; Mathematical models; Mixtures; Pistons; Pressure; Refrigerants; Temperature; Unsteady flow; Velocity; Energy equations; Mass flow rates; Momentum equations; Radial clearance; Rolling piston compressors; Transient flow; Compressors